Pengaruh Artificial Intelligence dalam Pembelajaran terhadap Self Management dengan Self Efficacy sebagai Variabel Mediasi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Padang - Dzaky Arobi; Rini Sarianti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the influence of artificial intelligence in learning on students' self-management, with self-efficacy as a mediating variable. The background of this research lies in the low ability of students to manage themselves effectively, which impacts delays in completing their studies. This is a causal research study. The population and sample consisted of students from the Faculty of Economics and Business at Universitas Negeri Padang. A total of 100 students were selected using cluster random sampling. Data were collected using a questionnaire with a Likert Scale. The analysis method employed was SEM-PLS using SmartPLS version 4.1.1 software. The results of the data analysis indicate that: (1) artificial intelligence in learning has a positive and significant effect on the self-management of FEB UNP students; (2) artificial intelligence in learning has a positive and significant effect on the self-efficacy of FEB UNP students; (3) self-efficacy has a positive and significant effect on the self-management of FEB UNP students; and (4) self-efficacy mediates the effect of artificial intelligence on the self-management of FEB UNP students.